Respon Pertumbuhan Bibit Kelapa Sawit di Pre Nusery terhadap Aplikasi Fungi Mikoriza Arbuskula dan Trichoderma pada Campuran Tanah Subsoil dan Bahan organik - Putra, Febbri Lestari Romeka; Wirianata, Herry; Wijayani, Suprih (Program Studi Agroteknologi INSTIPER, 2025)
The expansion and replanting of oil palm plantations require the availability of qualified seedlings to anticipate the biotic and abiotic stresses. The use of arbuscular mycorrhizal fungi (AMF) and Trichoderma biofertilizers is an alternative in the management of oil palm nurseries. This study is a factorial experiment arranged in a completely randomized design. There are three levels of AMF doses, namely: 0, 15, and 30 g/seedling; and there are three levels of Trichoderma doses, namely: 0, 10, and 15 g/seedling. There are nine treatment combinations with six replications, 54 pre-nursery oil palm seedlings are needed with seedling growth components and AMF colonization as observed parameters. The results of the study showed that the application of AMF 30 g/seedling and Trichoderma 15 g/seedling resulted in the highest level of mycorrhizal colonization in the roots of PN oil palm seedlings. The application of 30 g of AMF/seedling and 10 g of Trichoderma/seedling resulted in better biomass of PN oil palm seedlings, although not significantly different from the application of 15 g of AMF/seedling and 0 or 10 g of Trichoderma/seedling.